Flash Flood Disaster Mitigation Through Environmental Education - Prasetyo, Ketut (Geomatics and Environmental Engineering, 2022)
Flash flood disasters often hit many areas in Indonesia and can generate various losses. These conditions are exacerbated by people’s low knowledge and interest in their environment. Therefore, if people’s environmental education increases, especially their flood disaster mitigation knowledge, they can be prepared and better protect themselves from such disasters. People’s environmental education must start from determining the reason of the flood disaster in their environment to discovering how to avoid the disaster. This research design is a one-group post-test design. The collected data in this research is a written test result about knowledge in flash flood disaster mitigation materials as an implementation in environmental education in the community. The research data results were analyzed by means of simple regression, logistics regression, and correlation. Based on this research, environmental education with disaster mitigation materials has a high understanding level. In the disaster step, the highest understanding is before it happens. The correlation between educational strata and gender on environmental education and disaster mitigation materials is low. Finally, the role of women in disaster mitigation needs to improve because they have a higher understanding than males of disaster mitigation materials.